Formation of soliton trains in Bose-Einstein condensates as a nonlinear Fresnel diffraction of matter waves - Kamchatnov, A. M.; Gammal, A.; Abdullaev, F. K.; Kraenkel, Roberto André [UNESP] (Elsevier B.V., 2003)
The problem of generation of atomic soliton trains in elongated Bose-Einstein condensates is considered in framework of Whitham theory of modulations of nonlinear waves. Complete analytical solution is presented for the case when the initial density distribution has sharp enough boundaries. In this case the process of soliton train formation can be viewed as a nonlinear Fresnel diffraction of matter waves. Theoretical predictions are compared with results of numerical simulations of one- and three-dimensional Gross-Pitaevskii equation and with experimental data on formation of Bose-Einstein bright solitons in cigar-shaped traps. (C) 2003 Elsevier B.V. All rights reserved.